Characteristics and Functional Properties of Bioactive Oleogels: A Current Review - Md. Jannatul Ferdaus; Niaz Mahmud; Sudipta Talukder; Roberta Claro da Silva (Gels)
Oleogels have been a revolutionary innovation in food science in terms of their health benefits and unique structural properties. They provide a healthier alternative to traditional solid or animal fats. They have improved oxidative stability and nutritional value to maintain the desirable sensory qualities of lipid-based foods. Moreover, oleogels offer an ideal carrier for poorly water-soluble bioactive compounds. The three-dimensional structure of oleogels can protect and deliver bioactive compounds in functional food products. Bioactive compounds also affect the crystalline behavior of oleogelators, the physical properties of oleogels, and storage stability. Generally, different incorporation techniques are applied to entrap bioactive compounds in the oleogel matrix depending on their characteristics. These approaches enhance the bioavailability, controlled release, stability of bioactive compounds, and the shelf life of oleogels. The multifunctionality of oleogels extends their applications beyond fat replacements, e.g., food preservation, nutraceutical delivery, and even novel innovations like 3D food printing. Despite their potential, challenges such as large-scale production, cost efficiency, and consumer acceptance remain areas for further exploration. This review emphasizes the understanding of the relationship between the structure of oleogels and their functional properties to optimize their design in different food applications. It also highlights the latest advancements in bioactive oleogels, focusing on how they incorporate bioactive compounds such as polyphenols, essential oils, and flavonoids into oleogels. The impact of these compounds on the gelation process, storage stability, and overall functionality of oleogels is also critically examined.